Binding Energies in Atomic Negative Ions: II - Hotop, H.; Lineberger, W. C. (Journal of physical and chemical reference data, 1985)
This article updates a ten‐year‐old review of this subject [J. Chem. Phys. Ref. Data 4, 539 (1975)]. A survey of the electron affinity determinations for the elements up to Z=85 is presented, and based upon these data, a set of recommended electron affinities is established. Recent calculations of atomic electron affinities and the major semiempirical methods are discussed and compared with experiment. The experimental methods which yield electron binding energy data are described and intercompared. Fine structure splittings of these ions and excited state term energies are given.